Penegakan Hukum Administrasi Terhadap Reklamasi Pesisir Pantai Kota Ambon - Verlinando Tuhumena; Victor Juzuf Sedubun; Miracle Soplanit (Faculty of Law Universitas Pattimura, 2023)
ABSTRACT: Coastal reclamation is an example of human efforts to respond to limited land in urban areas as happened in Ambon City. In subsequent developments, the site was used for the construction of urban and banking facilities. The beach reclamation process has not actually been carried out properly so there are fears of negative impacts such as flooding, sedimentation. Changes in current patterns have not been identified, more and more material is washed away, resulting in silting of the waters and if this continues it will threaten the coastal ecosystem. The purpose of this study was to analyze and discuss whether the reclamation carried out on the coast of Ambon City had an impact on environmental damage and how Administrative Law enforcement on reclamation had an impact on environmental damage. The research method used was normative juridical research. The legal materials used are primary, secondary and tertiary legal materials. The results of this study need strict rules from the government from parties that have authority in dealing with beach reclamation issues carried out by certain parties.